Effect of Isopropanol on Microstructure and Activity of TiO2 Films with Dominant {001} Facets for Photocatalytic Degradation of Bezafibrate - Murtaza Sayed; Fu Pingfeng; Hasan M. Khan; Pengyi Zhang (International Journal of Photoenergy)
Titanium dioxide (TiO2) films with dominant {001} facets coated on a titanium sheet (Ti) were synthesized with the simple hydrothermal method by using Ti as the precursor and substrate. The effect of addition of isopropanol into the hydrothermal solution on the structure, photocatalytic activity, and stability of as-synthesized TiO2 films was investigated. The presence of isopropanol obviously influenced the microstructure of as-synthesized TiO2 films, which was converted from microspheres into irregular close stack of truncated tetrahedrons. And the percentage of exposed {001} facets calculated from the Raman spectra increased from 48.2% to 57%. Accordingly, the TiO2 films prepared with addition of isopropanol showed high and stable photocatalytic activity, which is nearly 2.6 times as that of the conventional P25 TiO2 coated on Ti-substrate. In addition, the photocatalytic activity of as-synthesized TiO2 films was greatly enhanced after calcination treatment at 600°C, which can be attributed to removal of fluoride ions and organic residuals adsorbed on the surface of the catalyst. Photoluminescence (PL) technique was used for the detection of produced hydroxyl radicals (•OH) on the surface of UV-illuminated TiO2 using terephthalic acid as probe molecule. The photocatalytic degradation intermediates of bezafibrate were analyzed by an ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), and accordingly the degradation pathways were proposed.